HIV-specific CD8 T cells express low levels of IL-7Ralpha: implications for HIV-specific T cell memory. - Wherry, E; Day, C; Draenert, R; Miller, J; Kiepiela, P; Woodberry, T; Brander, C; Addo, M; Klenerman, P; Ahmed, R; Walker, B (2006)
Chronic infections in mice can result in defects in memory CD8 T cell properties including low expression of the IL-7Ralpha (CD127). To determine whether defects in memory CD8 T cell formation exist during human chronic infections and to what extent these defects may be allele- or epitope-specific, we compared influenza (Flu), vaccinia (VV) and EBV-specific CD8 T cells to HIV-specific CD8 T cells, using a panel of 13 HIV tetramers. Compared to Flu, VV or EBV, HIV tetramer+ CD8 T cells expressed significantly lower levels of CD127, and this reduction was pervasive across all epitopes and alleles tested and over a wide range of viral loads and CD4 counts. These results indicate impaired HIV-specific memory CD8 T cell differentiation, regardless of level of control of viremia, epitopes targeted or restricting HLA alleles.